2016
DOI: 10.1186/s13287-016-0417-x
|View full text |Cite|
|
Sign up to set email alerts
|

Composite cell sheet for periodontal regeneration: crosstalk between different types of MSCs in cell sheet facilitates complex periodontal-like tissue regeneration

Abstract: BackgroundTissue-engineering strategies based on mesenchymal stem cells (MSCs) and cell sheets have been widely used for periodontal tissue regeneration. However, given the complexity in periodontal structure, the regeneration methods using a single species of MSC could not fulfill the requirement for periodontal regeneration.MethodsWe researched the interaction between the periodontal ligament stem cells (PDLSCs) and jaw bone marrow-derived mesenchymal stem cells (JBMMSCs), and constructed a composite cell sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 56 publications
0
40
0
1
Order By: Relevance
“…In this study, our primary goal was to investigate the effect of bilayer delivered from our thermosensitive hydrogels on angiogenic effect, and thus, we used nude mice. Although numerous studies using stem cell have been known to use immunocompetent mice, considerable number of researches still use nude mice for evaluation of therapeutic and functional efficiency . It should also be noted that HUVECs used in our study may be valid as a physiological model, but may not be used in the clinical setting and endothelial progenitors derived from human peripheral blood mononuclear cells (hPBMNCs) or umbilical cord blood‐mononuclear cells (UCB‐MNCs) may represent a potential therapeutic source.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, our primary goal was to investigate the effect of bilayer delivered from our thermosensitive hydrogels on angiogenic effect, and thus, we used nude mice. Although numerous studies using stem cell have been known to use immunocompetent mice, considerable number of researches still use nude mice for evaluation of therapeutic and functional efficiency . It should also be noted that HUVECs used in our study may be valid as a physiological model, but may not be used in the clinical setting and endothelial progenitors derived from human peripheral blood mononuclear cells (hPBMNCs) or umbilical cord blood‐mononuclear cells (UCB‐MNCs) may represent a potential therapeutic source.…”
Section: Resultsmentioning
confidence: 99%
“…A) . Similarly, cell sheets comprising PDLSCs and/or jaw BMMSCs have been multilayered to regenerate a complex periodontium‐like architecture . Recently, a “sandwich” tissue engineering complex was constructed by adding a layer of mineralized membrane on each side of the collagen membrane.…”
Section: Periodontal Tissue Engineering Via In Vitro Cell‐materials Dementioning
confidence: 99%
“…( A): Three‐layered cell sheets together with woven PGA and porous β‐TCP were used to repair three‐wall infrabony defects in dogs (please refer to the original source for more information). ( B): Schematic representation of a generated sandwich complex including (i) an engineered membrane (Bio‐Gide collagen membrane seeded with cells on both sides and cultured without the addition of mineralization‐induction medium) and (ii) two mineralized membranes (a cellular small intestinal submucosa in which cells are seeded on one side and cultured in mineralization‐induction medium for 8 days); (iii and iv) a sandwich structure was obtained by placing a cell‐seeded periodontal membrane between the two cell‐seeded/mineralized membranes (please refer to the original source for more details). Abbreviations: PGA, polyglycolic acid; β‐TCP, β‐tricalcium phosphate.…”
Section: Periodontal Tissue Engineering Via In Vitro Cell‐materials Dementioning
confidence: 99%
“…Osseointegration is enhanced by a series of surface modications, such as grit-blasting/thermo-chemical treatment, 1 grit-blasting/acid etching, 2 electrodeposits, 3 deposition by lasers, 4 and microarc oxidation. 5 Many studies have investigated the feasibility of applying cell sheets to bone regeneration, 6 cardiac regeneration, 7 cartilage regeneration, 8 tendon healing, 9 corneal regeneration, 10 esophageal regeneration, 11 periodontal regeneration, 12 and full thickness skin wound repair. 13 Recently, some studies 14,15 have reported bone marrow mesenchymal stem cell sheets (BMSC sheets) as a powerful tool for bioengineering applications in accelerating osseointegration.…”
Section: Introductionmentioning
confidence: 99%